Teaching Sexual Orientation and Gender Identity in Pediatric Clinical Settings: A Training Workshop for Faculty and Residents - Caroline R. Paul; Adam D. Wolfe; Marina Catallozzi; Thanakorn Jirasevijinda; Eric Kutscher; Brian Lurie (Association of American Medical Colleges, 2021)
Introduction Health disparities for the lesbian, gay, bisexual, transgender, queer, intersex, asexual, all other genders, sexes, and sexualities (LGBTQIA+) population are striking. Yet, deliberate efforts to integrate sexual orientation and gender identity in pediatric education settings remain lacking. The type of formal training that pediatric educators currently have for teaching of sexual orientation and gender identity is unclear and limited, which led to the development and implementation of this curriculum. Methods A 2-hour workshop was developed to address gaps in knowledge, equip faculty and resident educators with skills to apply key concepts in teaching activities, and motivate them to examine challenges and opportunities in teaching sexual orientation and gender identity principles in their routine duties in pediatric settings across the undergraduate and graduate education spectrum. Learning strategies of the workshop included learner activation, a didactic, and clinical cases with role-play opportunities. Participants completed evaluations at the end of the workshop. Results The workshop was implemented in three varied educational settings in 2019. All 65 participants enrolled in the workshop completed the evaluations. Evaluations ranged from 4.6 to 4.9 on a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree). Participants reported workshop strengths and anticipated impact on their own teaching and clinical practice. Discussion Stark health disparities for the LGBTQIA+ population and gaps in relevant curricula demand a training intervention for pediatric educators. We demonstrated the successful implementation of a training workshop, with evidence of feasibility and generalizability, that addressed knowledge gaps and teaching and clinical skills.